Updating Genograms in the Practice of Preventive Medicine - Allderdice, P.W. (1988)
Family physicians uncover clues to genetic risk while they routinely sketch and add to patients' genograms. A symbolic international language identifies health conditions and shows inter- and intra-generational relationships of mating and descent. Time allotted to reviewing the genogram and follow-up carried out by the family physician and/or through referral to a genetics clinic lie well within the mandate to practise preventive medicine. Such vigilance is fundamental to the unwritten agreement between the family and the family physician to delay, moderate, or avoid health crises.